The encouraging the heart : - Kouzes, James M. (Jossey-Bass, 2006)
Getting things done in today’s workplace is hard work. Employees become exhausted, frustrated, and sometimes entirely disenchanted–and often, they are tempted to simply give up. But the research conducted by Jim Kouzes and Barry Posner over the last two decades clearly shows that successful leaders find ways to combat these negative feelings by encouraging the hearts of their team members. This workbook, based on the model presented in the bestselling book Encouraging the Heart, guides readers through seven essentials of encouraging the heart: set clear standards, expect the best, pay attention, personalize recognition, tell the story, celebrate together, and set the example. The authors also provide a 21-question self-assessment to help leaders determine how they are doing and where they should focus their development efforts.